Constant-force photonic projectile for long-distance targeting delivery - Meng Chun; Ren Yu-Xuan; Lu Fengya; Yu Panpan; Zhou Jinhua; Zhong Min-Cheng (Nanophotonics)
Optically controllable delivery of microparticles excites interesting research and applications in various fields because of the noninvasive and noncontact features. However, long-distance delivery with a static low-power light source remains challenging. Here, the constant-force photonic projectile (CFPP) is employed to achieve long-distance delivery of microparticles with a low-power laser beam. The CFPP takes advantage of photon absorption to create a constant optical force within a large range, surpassing traditional tweezers. The concept of CFPP has been experimentally corroborated by remote control over micrometer-sized absorptive particles (APs) using a simple tilted focused beam. At the laser focus, strong photon absorption results in a large constant optical force that ejects the APs along the optical axis. Furthermore, the additional thermal convection field, which attracts particles from a distance into the working range of the CFPP, is utilized to collect the unbound APs for reuse. Finally, we demonstrate the concept of drug delivery by transporting a small microparticle onto a host particle at a remote location. The proposed CFPP provides a new perspective for drug delivery and heat-enhanced photodynamic therapy.